(untitled) (Docentes 2.0 Journal, 2021)
March 2020 marked us all, but it started shaking the schooled sector’s immune system. However, to understand the strategies Academy applied to address the problem, one must understand the factors presented at the beginning of the pandemic. In this sense, the research that concerns it gives an account of digital ethnographic analysis. Part of a general presentation of the pre-pandemic digital educational context in Mexico and finally focuses on the autonomous university context. It aims to publicize the first actions implemented by different autonomous universities. It collects information derived from digital sources exposed on social networks such as video tips and university councils’ reporting. Four autonomous universities are analyzed, and the information presented to official media is contrasted with data obtained through user surveys. The results present the constant and elements of three axes. The first points to the pre-pandemic social context immediately encompass academic decision-making for the community’s organization and end with the actions taken on universities’ virtual return. Finally, it invites the construction and incorporation of other knowledge that contribute to hybrid feature curriculums.